2021
DOI: 10.1109/access.2021.3114360
|View full text |Cite
|
Sign up to set email alerts
|

REFICS: Assimilating Data-Driven Paradigms Into Reverse Engineering and Hardware Assurance on Integrated Circuits

Abstract: Comprehensive hardware assurance approaches guaranteeing trust on Integrated Circuits (ICs) typically require the verification of the IC design layout and functionality through destructive Reverse Engineering (RE). It is a resource intensive process that will benefit greatly from the extensive integration of data-driven paradigms, especially in the imaging and image analysis phase. Although obvious, this uptake of data-driven approaches into RE-assisted hardware assurance is lagging due to the lack of massive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 87 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Therefore, full image reconstruction by sequential image tiles containing local topographic information draws intense research interest in cases where the required inspection area exceeds the maximum imaging area (Rong et al, 2009; Zukić et al, 2021). Image stitching provides a global appearance of the sample, which facilitates the analysis of the full pattern and affects the subsequent quality evaluation of the product (Ma et al, 2007; Wilson et al, 2021). Stitching is also meaningful in other application fields, including the analysis of biological tissues (Rankov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, full image reconstruction by sequential image tiles containing local topographic information draws intense research interest in cases where the required inspection area exceeds the maximum imaging area (Rong et al, 2009; Zukić et al, 2021). Image stitching provides a global appearance of the sample, which facilitates the analysis of the full pattern and affects the subsequent quality evaluation of the product (Ma et al, 2007; Wilson et al, 2021). Stitching is also meaningful in other application fields, including the analysis of biological tissues (Rankov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The different layers need to be aligned precisely for 3D reconstruction. For such inspections, SEM‐based overlay has been developed, which integrates high‐precision slicing as well as high‐resolution layer‐by‐layer imaging (Wilson et al, 2021). As a result, it is crucial to obtain large‐scale, high‐resolution, and high‐precision images of the full single‐layer structure by image stitching first.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity for this step stems from the introduction of artifacts during the layout extraction process. A detailed description of the artifacts and their sources were discussed in an earlier work [14]. A recent case study suggested that the time required for debugging the acquired data is much greater than the time frame required to image the entire IC [15].…”
Section: Introductionmentioning
confidence: 99%
“…A manufacturer may be interested in process control, particularly in the case of new processes in the research and development phase. In a world in which the design and manufacture of chips are sometimes conducted by different organizations spanning the globe, there is a need to verify the design or detect counterfeit designs [2][3][4] . Reverse engineering is an additional motivation 1 .…”
Section: Introductionmentioning
confidence: 99%